Otimização da distância de extração de madeira com forwarder - Malinovski, Ricardo Anselmo [UNESP]; Fenrier, Paulo Torres; Schack-Kirchner, Helmer; Malinovski, Jorge Roberto; Malinovski, E Rafael Alexandre (My University, 2008)
The activities and management operations of wood harvesting do not have good computational tools available to help the forest technicians with the task of cost reduction. In many cases, machines of high investment are used in wood harvesting without adequate operation planning; consequently, the cost per hour of these machines, which is high, could be reduced. Using technological resources such as the Geographic Information Systems (GIS) integrated with the Global Positioning System (GPS), which are the basis of precision harvesting. In this research, a technological tool capable of calculating and optimizing the average skidding distance of the forwarder was developed. It was used in stands of different sizes and formats through mathematical techniques and available functionalities in the Geographic Information System GRASS. The developed tool, called optimized model, divides the stand in small parts in relation to shorter skidding distances. The main variable considered was the alignment of plantation. The model was tested in eucalypt stands located in the State of São Paulo. Sixteen stands were randomly selected: eight with a rectangular polygon form, and eight with irregular polygon form. The main variables were collected in these stands. Results showed that the optimized model developed, is efficient and flexible. It was possible to divide the stands in small parts resulting in smaller skidding medium distances. The stands with irregular form had shorter skidding medium distances than the rectangular stands.
Optimization of skidding distance of wood with a forwarder
Keywords: Free software; GIS; Precision forestry; Wood harvesting; Computational tools; Different sizes; Management operations; Operation planning; Skidding distances; Technological resources; Technological tools; Computer graphics; Forestry; Geographic information systems; Global positioning system; Harvesting; Information systems; Investments; Optimization; Satellite navigation aids; Timber; Wood; Skidding; Computer Programs; Forests; Information Systems; Investment